The campus novel : regional or global? - Fuchs, Dieter, 1971-; Klepuszewski, Wojciech (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft ;, 2019)
"The Campus Novel - Regional or Global? presents innovative scholarship in the field of academic fiction. Whereas the campus novel is traditionally considered a product of the Anglo-American world, the present study opens a new perspective: it elucidates the intercultural exchange between the well-established Western canon of British and American academic fiction and its more recent regional response outside the Anglo-American territory."--